If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4(2x + 5) = -68 Reorder the terms: -4(5 + 2x) = -68 (5 * -4 + 2x * -4) = -68 (-20 + -8x) = -68 Solving -20 + -8x = -68 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '20' to each side of the equation. -20 + 20 + -8x = -68 + 20 Combine like terms: -20 + 20 = 0 0 + -8x = -68 + 20 -8x = -68 + 20 Combine like terms: -68 + 20 = -48 -8x = -48 Divide each side by '-8'. x = 6 Simplifying x = 6
| 6y-2/4=11-y/2 | | 1X+3X+10=20 | | m/0.8-(.2)^2=8.96 | | 4(-4-3x)=32 | | -4x-4(1+6x)=164 | | 4x+2(7-x)=24 | | 4x+2=3(2x+6) | | 3(x+2)=x+6(x-3) | | (2x+15)=61 | | 46/12 | | 6(7+3x)=32 | | 3*2a+3*2a=0 | | 5=3(2x-1)-3x | | 10=2(6-2x)+2x | | q^2-9q+14= | | 2-6x=6(1+2x) | | (0.267)(1000)= | | 2x+8+8x+22= | | (3-3a)(a^2-a-6)-(2a+2)(3-a)(a-3)-30(3-a)=0 | | 4x+28=2x+30 | | (-3.45)(2.1)= | | -3(x-4)=-(x-4) | | 2x+2-9=2(x+10) | | Y=1/9x-2 | | 2u=8/9 | | (b^2-9)= | | 3m+144=3m+2056 | | 1/2(6n-12)=3/4(4-8n | | 8x-5+3x=-5 | | 1/2(x-40)=45 | | (15x+30)+10=180 | | (c^2-36)= |